2023
DOI: 10.3390/land12101879
|View full text |Cite
|
Sign up to set email alerts
|

One Hundred Priority Questions for the Development of Sustainable Food Systems in Sub-Saharan Africa

Adam J. M. Devenish,
Petra Schmitter,
Nugun. P. Jellason
et al.

Abstract: Sub-Saharan Africa is facing an expected doubling of human population and tripling of food demand over the next quarter century, posing a range of severe environmental, political, and socio-economic challenges. In some cases, key Sustainable Development Goals (SDGs) are in direct conflict, raising difficult policy and funding decisions, particularly in relation to trade-offs between food production, social inequality, and ecosystem health. In this study, we used a horizon-scanning approach to identify 100 prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Green consumption was shown to be significantly and positively impacted by counteraction from ER. (3) This study used the amount of carbon sequestration by plants as another measure of carbon emissions because of the self-absorption effect of carbon emissions, and it was found that the capacity of vegetation to store carbon tends to increase and then decrease as green consumption increases; this effect will become stronger over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Green consumption was shown to be significantly and positively impacted by counteraction from ER. (3) This study used the amount of carbon sequestration by plants as another measure of carbon emissions because of the self-absorption effect of carbon emissions, and it was found that the capacity of vegetation to store carbon tends to increase and then decrease as green consumption increases; this effect will become stronger over time.…”
Section: Discussionmentioning
confidence: 99%
“…However, these two index systems differ from the actual situation in China; for example, the UNCSD only targets green commodities themselves and is less involved in the production and life of residents, so we need to build evaluation indicators that are in line with China's reality. Green consumption stems from sustainable development, which comprises three stages: the purchase, use, and disposal of products [3]. As a new consumption concept, it faces a series of new challenges and problems in practical exploration and theoretical research.…”
Section: Literature Reviewmentioning
confidence: 99%